Longitudinal analysis of occupational prestige in Switzerland, 1946–2023: navigating economic modernization and changing labor market conditions - Richard Nennstiel; Rolf Becker (Frontiers in Sociology)
This study examines the long-term impact of educational expansion, occupational restructuring, and economic modernization on the prestige trajectories of Swiss men and women from 1946 to 2023. The impacts of these macro trends on individuals' career prospects are discussed by applying different theoretical approaches used in labor market research, such as the human capital approach, signal and filter theory, the labor queue model, the vacancy competition model, as well as the theory of labor market segmentation. Using data from the Swiss Household Panel and historical macroeconomic indicators, we apply growth curve models to analyze how structural changes shape occupational prestige over the life course and we test several hypotheses derived from different theoretical approaches (e.g., human capital theory, signal and filter theory, skill-biased technological change, and the vacancy competition model). Our findings reveal significant differences between cohorts, with younger generations benefiting from educational expansion and the shift toward a service economy. While modernization and labor market conditions influence career entry prestige, the role of education has become increasingly decisive over time, mitigating adverse structural effects. Men's prestige trajectories are more sensitive to macroeconomic fluctuations, while women's career advancements are more strongly linked to educational investment. Cohort size effects indicate increased intra-cohort competition, particularly among men. The study highlights the interplay between individual qualifications and structural labor market constraints, emphasizing the importance of a dynamic micro-macro approach for understanding social mobility. These findings contribute to the broader discourse on occupational stratification and the long-term returns to education, in the context of modernizing labor markets.